ANALISIS PELAKSANAN PERWAKAFAN TANAH YANG TIDAK MEMENUHI SYARAT-SYARAT PADA UNDANG-UNDANG NOMOR 41 TAHUN 2004 TENTANG WAKAF DAN INTRUKSI PRESIDEN NOMOR 1 TANUN 1991 TENTANG KOMPILASI HUKUM ISLAM (Studi Putusan - Putusan Nomor 163/Pdt.G/2018/PTA.Bandung) - Ovannyalda Chrismananta; Mulati Mulati (Jurnal Hukum Adigama, 2020)
Based on the requirements of Waqf there is an issue that is in Kp. Magalayu, Citatah Village, District Citatah, West Bandung Regency. There is a plot area of 26,000 m2 that has been established by the school and public burial place. The land belongs to the local village government that was formerly a representative by the head of the former village to be represented. The Waqf is contrary to the prevailing laws and regulations in Indonesia, thus giving rise to conflict between the village government and its heirs. Based on the contents in this thesis there is the problem is how the implementation of land representatives who do not meet the requirements of the law No. 41 year 2004 about Waqf and Presidential instruction No. 1 year 1991 about the law compilation. The content of my thesis is based on the ruling that does not return the land to the village government when the land dispute is a village land, so according to the author of the Waqf should be cancelled because it does not comply with the prevailing laws and the Waqf is said to be haram. Furthermore, the research method is research for academic purposes, the method of approach used by the authors in the writing of this thesis is a legal approach, the research examined by the authors in this research is a prescriptive study.